Universiti Malaysia Pahang Inks MoU for Knowledge Sharing and Technology Transfer of Engineering and Technology - Irene, Wei Kiong Ting (QS Asia, 2019)
Universiti Malaysia Pahang (UMP) signed a Memorandum of Understanding (MoU) with BASF PETRONAS Chemicals Sdn. Bhd. (BPC) for more collaborations on transferring technology and knowledge-sharing for development in the fields of engineering and technology, as well as exchanging scientific expertise, all of which would be beneficial to not only UMP students for improving their competency and employability, but also industry partners from the perspective of reduction of the loss of explicit and tacit technical know-hows.